2006
DOI: 10.1002/acp.1280
|View full text |Cite
|
Sign up to set email alerts
|

Individual and developmental differences in eyewitness recall and suggestibility in children with intellectual disabilities

Abstract: This study examined two key issues: (1) whether there were developmental improvements in eyewitness memory performance for children with intellectual disabilities (ID); and (2) whether standardised measures of cognitive ability and suggestibility would relate to eyewitness recall and suggestibility. Children with ID and age-matched controls (ages 8/9 and 12 years) watched a video of a crime and were asked a range of open-ended and specific questions about the event in a subsequent interview. Free recall increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…Further, Burgwyn-Bailes et al (2001) reported that receptive vocabulary significantly predicted delayed (but not immediate) memory of an emergency medical procedure; a relationship that was stronger for younger than older children (age range 3-7 years). In a further study, receptive vocabulary was related to performance on general open-ended questions (and errors in both free and general recall), but not to free recall in children between the ages of 8 and 12 years (Henry & Gudjonsson, 2007).…”
Section: Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Further, Burgwyn-Bailes et al (2001) reported that receptive vocabulary significantly predicted delayed (but not immediate) memory of an emergency medical procedure; a relationship that was stronger for younger than older children (age range 3-7 years). In a further study, receptive vocabulary was related to performance on general open-ended questions (and errors in both free and general recall), but not to free recall in children between the ages of 8 and 12 years (Henry & Gudjonsson, 2007).…”
Section: Languagementioning
confidence: 99%
“…IQ has modest and variable relationships with eyewitness recall in TD children that change with age (e.g. Elischiberger & Roebers, 2001;Geddie, Fradin, & Beer, 2000;Henry & Gudjonsson, 2007;Roebers & Schneider, 2001). Although it is unclear whether similar relationships emerge in children with autism, the limited available research suggests they may not (Bruck et al, 2007).…”
Section: Age and Intelligence (Iq)mentioning
confidence: 99%
“…That is, individuals with higher IQ scores tend to have better memory skills and to provide more detailed recall when reporting an event Zhu et al, 2010). Although a legal professional might not need to take into account the intelligence of typically developing (TD) children, it is important to be aware that children who suffer from learning and other intellectual disabilities (ID) may be more vulnerable in forensic contexts (Henry & Gudjonsson, 2007). Indeed, the rate at which children's memory performance improves across age may be slower for ID children than for TD children, with mental age a better predictor of eyewitness memory performance than IQ measures (Henry & Gudjonsson, 2007).…”
Section: Vulnerability To Error and Influencementioning
confidence: 99%
“…Although a legal professional might not need to take into account the intelligence of typically developing (TD) children, it is important to be aware that children who suffer from learning and other intellectual disabilities (ID) may be more vulnerable in forensic contexts (Henry & Gudjonsson, 2007). Indeed, the rate at which children's memory performance improves across age may be slower for ID children than for TD children, with mental age a better predictor of eyewitness memory performance than IQ measures (Henry & Gudjonsson, 2007). Thus, children with ID are at risk of being less accurate and more suggestible in their event reporting than are TD children.…”
Section: Vulnerability To Error and Influencementioning
confidence: 99%
“…Reporting an incident to the police requires communication skills to explain what has happened. However, between 50 and 90% of people with ID suffer from communication difficulties (Jones ), and they may have limited speed of information processing (Henry & Gudjonsson ). This means that people with ID can be disadvantaged right from the start of the investigative process.…”
Section: Introductionmentioning
confidence: 99%